Introduction to the Global Coconut Strategy - Bourdeix, Roland; Stoian, D.; Johnson, V. (Bioversity International, 2018)
Chapter 1 introduces the background context and rationale for this new Global Strategy for the Conservation and Use of Coconut Genetic Resources. It articulates the origin, history and dynamics of coconut cultivation, particularly emphasising the importance of coconut genetic diversity and outlining the threats it faces. It then highlights the role of the International Coconut Genetic Resources Network (COGENT), and urgent need for this revised Global Strategy. The chapter then outlines the Strategy’s vision, goal, objectives, outputs and outcomes, and how these link with the CGIAR system-level outcomes (SLOs), and concludes with describing the participatory approach to developing the Strategy.